Implementation of Management Functions in Islamic Boarding School Cooperatives Based on Social-Religious Values - Hasanah, Titi Faridatun (IJoIS: Indonesian Journal of Islamic Studies, 2025)
This study uses a descriptive qualitative approach with data collection methods of interviews, documentation, and literature review to analyze the management of Islamic boarding school cooperatives based on social and religious values. The results show that the implementation of management functions such as planning, organizing, mobilizing, monitoring, and evaluation in cooperatives faces significant challenges related to human resources and financial transparency. This cooperative operates a retail outlet, laundry services, and sharia savings and loans that empower students and alumni in a sustainable manner. Research recommendations include strengthening management capabilities, improving administrative systems, and increasing member participation to enhance the professionalism and sustainability of Islamic boarding school cooperatives.